Global patient experience of paramedic practice. (2nd March 2019) - Perry, Matt; Usher, Kim; Jackson, Debra
Abstract : Background: Paramedics occupy an ever-increasing role within healthcare and the development of this role should be informed by the voice of patients. This systematic literature review seeks to explore patient experience during a paramedic intervention. Methods: Using a 'state of the art' review style, a systematic search was conducted of the literature published between 2006 and 2018. Following PRISMA guidelines, a total of seven articles meeting the inclusion criteria were identified. A definition of experience which incorporates several dimensions was used to frame the search. Results: Three themes were identified, with the available literature focusing mainly on satisfaction. Satisfaction is improved through certainty and clarity of the progression through treatment and is high among patients of paramedics. Conclusion: Our understanding of patient experience in paramedic interventions is largely limited to an understanding of satisfaction. While this may provide some useful insights, other facets such as the lived experience and physiologic aspects are underrepresented in the current evidence base.